Blended learning in higher education: Current and future challenges in surveying education - El-Mowafy, Ahmed; Kuhn, M.; Snow, T. (Western Australian Institute for Educational Research Inc, 2013)
The development of a blended learning approach to enhance surveying education is discussed. The need for this learning strategy is first investigated based on a major review of the surveying course, including analysis of its content, benchmarking with key national and international universities, and surveys of key stakeholders. Appropriate blended learning methods and tools that couple learning theory principles and developing technical skills are discussed including using learning management systems, flip teaching, collaborative learning, simulation based e-learning, and peer assessment. Two blended learning tools developed for surveying units are presented as examples. The first is an online interactive virtual simulation tool for levelling, one of the key tasks in surveying. The second is an e-assessment digital marking, moderation and feedback module. Surveys of students showed that they found the interactive simulation tool contributes to improving their understanding of required tasks. Students also found the e-assessment tool helpful in improving their performance and in helping them to focus on the objectives of each activity. In addition, the use of peer e-assessment to improve student learning and as a diagnostic tool for tutors is demonstrated. The paper concludes with a discussion on developing generic skills through authentic learning in surveying education.